A sodium ion battery positive electrode nanomaterial and its use in vehicles
The composite sodium iron phosphate material was synthesized by spray drying and high-temperature annealing, and a C-clad layer was formed through ball milling and high-temperature carbonization, which solved the problem of insufficient electrochemical performance of sodium ion battery materials and achieved improvement in capacity and efficiency.
Patent Information
- Application Number
- CN202411103538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The existing polyanionic sodium ion battery materials have limited their application in sodium ion batteries due to their low conductivity and limited capacity, especially the electrochemical performance of Na3.12Fe2.44 (P2O7)2 needs to be further improved.
The composite sodium iron phosphate material NaxFey(PO4)2P2O7 was synthesized by spray drying and high-temperature annealing, and a C-clad layer was formed by ball milling and high-temperature carbonization treatment to form a sodium ion battery nano-positive material Na3.64Fe2.91(PO4)2P2O7@ C, improve its electrochemical properties.
The capacity, first-time Coulomb efficiency and capacity retention of the cathode material of sodium ion battery are significantly improved, the electrochemical performance is improved, and the process is simple, and it does not involve flammable and explosive reactants.
Smart Images

Figure CN118645606B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery positive electrode nanomaterials, and in particular to a sodium ion battery positive electrode nanomaterial and application thereof in a vehicle. Background Art
[0002] Room temperature sodium-ion batteries (SIBS) are promising candidates for smart grids and large-scale energy storage systems due to their abundant and inexpensive sodium resources. Among the high-performance SIBS electrode materials developed so far, layered transition metal oxides and polyanionic materials are considered to be the most attractive options. In contrast, due to the inductive effect of the polyanionic groups, the operating potential of polyanionic materials is higher. The solid 3D framework greatly reduces the structural changes during the de / intercalation of sodium ions. In addition, the effect of strong XO (XS, P, Si, etc.) covalent bonds can effectively inhibit oxygen evolution. Due to these advantages, polyanionic materials have higher cycle stability and higher safety. However, low conductivity and limited capacity still limit their further application. K.Ha et al. demonstrated that Na 3.12 Fe 2.44 The electrochemical performance of (P2O7)2 is good, but the presence of large pyrophosphate groups is not conducive to further improving the theoretical specific capacity of the material. Therefore, a technology to improve the electrochemical performance of this material is urgently needed.
[0003] C coating can improve the electronic conductivity of the composite material and effectively protect the core structure of NFPP from being damaged during electrochemical cycles. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a sodium ion battery positive electrode nanomaterial and uses thereof, so as to improve the capacity, first coulombic efficiency and capacity retention rate of the sodium ion battery positive electrode nanomaterial.
[0005] In order to solve the above technical problems, the present invention specifically provides the following technical solutions:
[0006] The invention discloses a sodium ion battery nano cathode material, comprising: a composite sodium iron phosphate material of a core layer and a C material coated on an outer layer; the structure of the composite sodium iron phosphate material is Na x Fe y (PO4)2P2O7, wherein x is 1-6 and y is 1-5.
[0007] Preferably, x is 3-4, and y is 2-3; or, x is 3.64, and y is 2.91.
[0008] Preferably, the C material is formed by carbonization of oleic acid or oleic acid ester. Oleic acid ester can reduce Na 3.64 Fe 2.91The friction between (PO4)2P2O7 powders improves the mixing uniformity, thereby improving the dispersion of materials during the ball milling process, which helps to form a more uniform composite material. During the high-temperature carbonization process, it decomposes and forms a carbon coating layer, which effectively inhibits the growth and agglomeration of material particles, obtains a composite material with good dispersion and small particles, and improves the electrochemical performance of the positive electrode material of sodium ion batteries.
[0009] The present invention discloses a method for preparing a nano cathode material for a sodium ion battery, comprising:
[0010] S1: The composite sodium iron phosphate raw material is synthesized by spray drying and high temperature annealing to form the composite sodium iron phosphate material, namely Na x Fe y (PO4)2P2O7, wherein x is 1-6 and y is 1-5;
[0011] S2: The composite sodium iron phosphate material and the C coating material are mixed and carbonized at high temperature to form Na x Fe y (PO4)2P2O7@C is the nano positive electrode material for sodium ion batteries.
[0012] Preferably, the composite sodium iron phosphate material and the C coating material are mixed by ball milling.
[0013] Preferably, the composite sodium iron phosphate raw material includes NaH2PO4·2H2O, C6H8O7·H2O, Fe(NO3)3·9H2O and water.
[0014] More preferably, the usage ratio of NaH2PO4·2H2O to water is 0.0002-0.003 mol / mL, the usage ratio of C6H8O7·H2O to water is 0.0002-0.003 mol / mL, and the usage ratio of Fe(NO3)3·9H2O to water is 0.0001-0.002 mol / mL; or, C6H8O7·H2O is citric acid monohydrate. Citric acid has the ability to form complexes with metal ions. In the process of synthesizing composite sodium iron phosphate materials, citric acid can form complexes with metal ions such as iron ions, which not only helps to stabilize metal ions, but also promotes the reaction and accurately controls the reaction rate and product selectivity. Citric acid can control the morphology and performance of the catalyst or material by adjusting the pH value. Citric acid can also make the catalyst or material particles evenly dispersed in the solution, thereby improving the dispersion of the catalyst or material and enhancing the catalytic efficiency or reaction activity.
[0015] Preferably, the temperature of the spray drying method is 80-120°C; or, the high temperature annealing method is annealing at 200-400°C under argon / hydrogen flow for 2-8 h.
[0016] Preferably, the C coating material comprises oleic acid or oleate, wherein the oleate is made of oleic acid and butyric acid glyceride.
[0017] Preferably, Na 3.64 Fe 2.91 (PO4)2P2O7 and C coating material are mixed in a mass ratio of 1:0.5-5.
[0018] The invention discloses a battery, comprising the above-mentioned sodium ion battery nano positive electrode material or the sodium ion battery nano positive electrode material prepared by the above-mentioned method.
[0019] The invention discloses a vehicle, comprising the battery.
[0020] A method for preparing a sodium ion battery positive electrode nanomaterial, the specific steps of which are:
[0021] S1: Na 3.64 Fe 2.91 (PO4)2P2O7 was synthesized by spray drying and high temperature annealing. NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were added into water and stirred and mixed. The mixture was spray dried at 80-120 °C to obtain a powder precursor. The powder precursor was then annealed at 200-400 °C for 2-8 h under a mixed gas flow of hydrogen and argon with a volume ratio of 1:20-50 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7.
[0022] S2: Na 3.64 Fe 2.91 Preparation of (PO4)2P2O7@C, Na obtained from S1 3.64 Fe 2.91 (PO4)2P2O7 and C-coated materials were mixed by ball milling under argon for 12-36 h, dried under inert atmosphere, heated to 500-600 °C, and carbonized at high temperature for 5-15 h to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C.
[0023] Preferably, in the above technical solution, in step S1, the amount of NaH2PO4·2H2O added to distilled water is 0.0002-0.003 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.0002-0.003 mol / mL, and the amount of Fe(NO3)3·9H2O added to distilled water is 0.0001-0.002 mol / mL.
[0024] Preferably, in the above technical solution, in step S2, Na 3.64 Fe2.91 (PO4)2P2O7 and C coating material are mixed in a mass ratio of 1:0.5-5.
[0025] Preferably, in the above technical solution, the C coating material in step S2 includes at least one of oleic acid and oleic acid esters, and during the ball milling process, the C coating material and Na 3.64 Fe 2.91 (PO4)2P2O7 forms a stable coating structure, and in the subsequent high-temperature carbonization process, a uniform and stable Na 3.64 Fe 2.91 (PO4)2P2O7@C is a nanomaterial for the positive electrode of sodium ion batteries. By adjusting the type and amount of C coating materials, the Na 3.64 Fe 2.91 Optimization of properties of (PO4)2P2O7@C composite materials.
[0026] Preferably, in a preferred embodiment of the present invention, the preparation of the positive electrode material for a sodium ion battery is as follows: first, Na 3.64 Fe 2.91 (PO4)2P2O7. NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water, stirred at room temperature to obtain a mixed stock solution, and the mixed stock solution was spray-dried at 80-120 °C to obtain a powder precursor. Then, the powder precursor was annealed at 200-400 °C for 2-8 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20-50 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91 (PO4)2P2O7 and oleic acid were ball-milled and mixed under argon for 12-36 h, dried under an inert atmosphere, and heated to 500-600 °C for carbonization for 5-15 h to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C, the positive electrode material of sodium ion battery, is under an inert atmosphere of argon.
[0027] More preferably, in the above preferred embodiment, the amount of NaH2PO4·2H2O added to distilled water is 0.0002-0.003 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.0002-0.002 mol / mL, the amount of Fe(NO3)3·9H2O added to distilled water is 0.0001-0.0015 mol / mL, and the amount of Na 3.64 Fe 2.91(PO4)2P2O7 and oleic acid are mixed in a mass ratio of 1:0.5-4.
[0028] More preferably, in the present invention, when preparing the positive electrode material for sodium ion batteries, oleic acid can be replaced by oleic acid ester.
[0029] The invention discloses a method for preparing oleic acid ester.
[0030] More preferably, the preparation method of oleate is specifically as follows:
[0031] Oleic acid and butyric acid glyceride are used to carry out esterification reaction to synthesize oleic acid esters. Oleic acid and butyric acid glyceride are mixed, and p-toluenesulfonic acid monohydrate is added as a catalyst. Stir evenly under nitrogen environment and react at 50-100 ℃ for 4-10 hours and then cool to room temperature. Then, ethyl acetate and water are added for multiple extractions, and then the organic phase is washed with water until it is neutral, the organic phase is collected and anhydrous sodium sulfate is added to remove water, and the solvent ethyl acetate is removed by suction filtration and rotary evaporation to obtain oleic acid esters.
[0032] Preferably, in the method for preparing oleic acid esters, the mass ratio of oleic acid to butyric acid glyceride is 1:1-3, and the mass ratio of p-toluenesulfonic acid monohydrate to oleic acid is 1:25-35.
[0033] More preferably, in the present invention, isooctyl palmitate can also be added when preparing the positive electrode material of the sodium ion battery. On the basis of using oleic acid ester, isooctyl palmitate can be further used to effectively protect the Na 3.64 Fe 2.91 The core structure of (PO4)2P2O7 improves the stability of the core structure and prevents it from being destroyed during the electrochemical cycle. It can also further improve the carbon coating efficiency and the electrochemical performance of the positive electrode material of the sodium ion battery.
[0034] Preferably, in a preferred embodiment of the present invention, the preparation of the positive electrode material for a sodium ion battery is as follows: first, Na 3.64 Fe 2.91 (PO4)2P2O7. NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water, stirred at room temperature to obtain a mixed stock solution, and the mixed stock solution was spray-dried at 80-120 °C to obtain a powder precursor. Then, the powder precursor was annealed at 200-400 °C for 2-8 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20-50 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91(PO4)2P2O7, oleate and isooctyl palmitate were ball-milled for 12-36 h under argon, dried under an inert atmosphere, and heated to 500-600 °C for carbonization for 5-15 h to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C, the positive electrode material of sodium ion battery, is under an inert atmosphere of argon.
[0035] More preferably, in the above preferred embodiment, the amount of NaH2PO4·2H2O added to distilled water is 0.0002-0.003 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.0002-0.002 mol / mL, the amount of Fe(NO3)3·9H2O added to distilled water is 0.0001-0.0015 mol / mL, and the amount of Na 3.64 Fe 2.91 The usage of (PO4)2P2O7 and oleate is in a mass ratio of 1:0.5-4, Na 3.64 Fe 2.91 The usage ratio of (PO4)2P2O7 and isooctyl palmitate is 1:0.2-1.5 by mass.
[0036] The invention also discloses a use of the sodium ion battery positive electrode nano material in preparing a battery.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The present invention proposes a sodium ion battery positive electrode nanomaterial, which is synthesized by spray drying and high temperature annealing. 3.64 Fe 2.91 (PO4)2P2O7, with good crystallinity and purity, was prepared by ball milling and high-temperature carbonization with C-coated materials to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C, i.e., the positive electrode nanomaterial of sodium ion battery, has achieved complete coverage of C coating material, and the chemical reaction is easy to carry out. The whole preparation process is simple and does not involve flammable and explosive reactants. 3.64 Fe 2.91 The capacity, initial efficiency and capacity retention rate of the (PO4)2P2O7@C prepared battery were effectively improved, thereby improving its electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0040] Figure 1 is the infrared spectrum of oleate;
[0041] Figure 2 This is a scanning electron microscope analysis of the positive electrode nanomaterial of the sodium ion battery;
[0042] Figure 3 A diagram of the discharge capacity of a half-cell made of nanomaterials for the positive electrode of a sodium-ion battery;
[0043] Figure 4 Cycling performance diagram of half-cell made of nanomaterials for sodium-ion battery cathode;
[0044] Figure 5 This is the cycling performance diagram of a half-cell made of sodium-ion battery positive electrode nanomaterials at 60°C. DETAILED DESCRIPTION
[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] The following first describes the concepts involved in the present application in conjunction with the accompanying drawings. It should be noted that the following description of each concept is only to make the content of the present application easier to understand, and does not limit the scope of protection of the present application; at the same time, the embodiments and features in the embodiments of the present application can be combined with each other in the absence of conflict. The present application will be described in detail with reference to the accompanying drawings and in conjunction with the embodiments.
[0047] Embodiment 1:
[0048] Preparation of positive electrode materials for sodium ion batteries: First, Na 3.64 Fe 2.91(PO4)2P2O7. NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water and stirred at room temperature to obtain a mixed stock solution, which was then spray dried at 105 °C to obtain a powder precursor. The powder precursor was then annealed at 300 °C for 6 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91 (PO4)2P2O7 and oleic acid were ball-milled under argon for 24 h, dried under an inert atmosphere, and heated to 550 °C for 10 h to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C is the positive electrode material of sodium ion battery. The amount of NaH2PO4·2H2O added to distilled water is 0.00067 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.00067 mol / mL, the amount of Fe(NO3)3·9H2O added to distilled water is 0.0005 mol / mL, and the amount of Na 3.64 Fe 2.91 (PO4)2P2O7 and oleic acid were mixed in a mass ratio of 1:1 under an inert atmosphere of argon.
[0049] Embodiment 2:
[0050] Preparation of oleic acid esters: Oleic acid and butyric acid glyceride are used to synthesize oleic acid esters by esterification reaction. Oleic acid and butyric acid glyceride are added and mixed in sequence, and p-toluenesulfonic acid monohydrate is added as a catalyst. Stir evenly under nitrogen environment to obtain a mixed solution. The mixed solution is continued to react at 60 ° C under nitrogen environment with stirring for 6 h and then cooled to room temperature. Subsequently, ethyl acetate and distilled water are added for multiple extractions. After the organic phase is washed with distilled water until neutral, the organic phase is collected and anhydrous sodium sulfate is added to remove water. The solvent ethyl acetate is removed by suction filtration and rotary evaporation to obtain oleic acid esters. The mass ratio of oleic acid to butyric acid glyceride is 1:1.3, and the mass ratio of p-toluenesulfonic acid monohydrate to oleic acid is 1:29.7.
[0051] Preparation of positive electrode material for sodium ion battery: The preparation of positive electrode material for sodium ion battery in this embodiment is compared with that in Example 1, except that oleic acid is replaced with oleic acid ester prepared in this embodiment, and other conditions are the same as those in Example 1, and Na 3.64 Fe 2.91 (PO4)2P2O7@C, which is the positive electrode material of sodium ion battery.
[0052] Embodiment 3:
[0053] The preparation of oleate is the same as in Example 2.
[0054] Preparation of positive electrode materials for sodium ion batteries: First, NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water, stirred at room temperature to obtain a mixed stock solution, and the mixed stock solution was spray-dried at 105 °C to obtain a powder precursor. Then, the powder precursor was annealed at 300 °C for 6 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91 (PO4)2P2O7 and oleic acid were ball-milled under argon for 24 h, dried under an inert atmosphere, and heated to 550 °C for 10 h to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C is the positive electrode material of sodium ion battery. The amount of NaH2PO4·2H2O added to distilled water is 0.00067 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.00067 mol / mL, the amount of Fe(NO3)3·9H2O added to distilled water is 0.0005 mol / mL, and the amount of Na 3.64 Fe 2.91 (PO4)2P2O7 and oleate are mixed in a mass ratio of 1:0.7 under an inert atmosphere of argon.
[0055] Embodiment 4:
[0056] The preparation of oleate is the same as in Example 2.
[0057] Preparation of positive electrode materials for sodium ion batteries: First, NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water, stirred at room temperature to obtain a mixed stock solution, and the mixed stock solution was spray-dried at 105 °C to obtain a powder precursor. Then, the powder precursor was annealed at 300 °C for 6 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91 (PO4)2P2O7 and oleic acid were ball-milled under argon for 24 h, dried under an inert atmosphere, and heated to 550 °C for 10 h to obtain Na 3.64 Fe 2.91(PO4)2P2O7@C is the positive electrode material of sodium ion battery. The amount of NaH2PO4·2H2O added to distilled water is 0.00067 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.00067 mol / mL, the amount of Fe(NO3)3·9H2O added to distilled water is 0.0005 mol / mL, and the amount of Na 3.64 Fe 2.91 (PO4)2P2O7 and oleate are mixed in a mass ratio of 1:3 under an inert atmosphere of argon.
[0058] Embodiment 5:
[0059] The preparation of oleate is the same as in Example 2.
[0060] Preparation of positive electrode materials for sodium ion batteries: First, NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water, stirred at room temperature to obtain a mixed stock solution, and the mixed stock solution was spray-dried at 105 °C to obtain a powder precursor. Then, the powder precursor was annealed at 300 °C for 6 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91 (PO4)2P2O7, oleate and isooctyl palmitate were ball-milled for 24 h under argon, dried under an inert atmosphere, and carbonized at 550 °C for 10 h to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C is the positive electrode material of sodium ion battery. The amount of NaH2PO4·2H2O added to distilled water is 0.00067 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.00067 mol / mL, and the amount of Fe(NO3)3·9H2O added to distilled water is 0.0005 mol / mL; Na 3.64 Fe 2.91 The mass ratio of (PO4)2P2O7 and oleate is 1:0.5, Na 3.64 Fe 2.91 The usage ratio of (PO4)2P2O7 and isooctyl palmitate is 1:0.5 by mass, and the inert atmosphere is argon atmosphere.
[0061] Embodiment 6:
[0062] The preparation of oleate is the same as in Example 2.
[0063] Preparation of positive electrode materials for sodium ion batteries: First, NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water, stirred at room temperature to obtain a mixed stock solution, and the mixed stock solution was spray-dried at 105 °C to obtain a powder precursor. Then, the powder precursor was annealed at 300 °C for 6 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91 (PO4)2P2O7, oleate and isooctyl palmitate were ball-milled for 24 h under argon, dried under an inert atmosphere, and carbonized at 550 °C for 10 h to obtain Na 3.64 Fe 2.91 (PO4)2P2O7@C is the positive electrode material of sodium ion battery. The amount of NaH2PO4·2H2O added to distilled water is 0.00067 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.00067 mol / mL, and the amount of Fe(NO3)3·9H2O added to distilled water is 0.0005 mol / mL; Na 3.64 Fe 2.91 The mass ratio of (PO4)2P2O7 and oleate is 1:0.5, Na 3.64 Fe 2.91 The usage ratio of (PO4)2P2O7 and isooctyl palmitate is 1:1 by mass, and the inert atmosphere is argon atmosphere.
[0064] Comparative Example 1:
[0065] The preparation of oleate is the same as in Example 2.
[0066] Preparation of positive electrode materials for sodium ion batteries: First, NaH2PO4·2H2O, C6H8O7·H2O and Fe(NO3)3·9H2O were dissolved in distilled water, stirred at room temperature to obtain a mixed stock solution, and the mixed stock solution was spray-dried at 105 °C to obtain a powder precursor. Then, the powder precursor was annealed at 300 °C for 6 h under a mixed flow of hydrogen and argon with a volume ratio of 1:20 to obtain Na 3.64 Fe 2.91 (PO4)2P2O7. Then Na 3.64 Fe 2.91 (PO4)2P2O7, oleic acid and oleate were mixed by ball milling under argon for 24 h, dried under inert atmosphere, and heated to 550 °C for 10 h to obtain Na 3.64 Fe 2.91(PO4)2P2O7@C is the positive electrode material of sodium ion battery. The amount of NaH2PO4·2H2O added to distilled water is 0.00067 mol / mL, the amount of C6H8O7·H2O added to distilled water is 0.00067 mol / mL, the amount of Fe(NO3)3·9H2O added to distilled water is 0.0005 mol / mL, and the amount of Na 3.64 Fe 2.91 The mass ratio of (PO4)2P2O7 and oleic acid is 1:0.8, Na 3.64 Fe 2.91 The mass ratio of (PO4)2P2O7 and oleate was 1:0.2, and the inert atmosphere was argon.
[0067] Experimental Example 1:
[0068] To characterize the oleate, the oleate prepared in Example 2 was subjected to infrared spectroscopy analysis. The oleate was dissolved in ethanol and evenly coated on a pre-pressed KBr sheet. The scanning range was 500-4000 cm -1 The results are as follows Figure 1 As shown, among them, at 1700-1750 cm -1 Range, representing the C=O stretching vibration absorption peak of ester. At 1000-1300cm -1 The stretching vibration peak of CO bond can be seen between 2850-2950 cm -1 In the range of 1600-1680 cm -1 Range, representing the C=C absorption peak. At 3200-3600 cm -1 The range is the absorption peak of OH.
[0069] Experimental Example 2:
[0070] The sodium ion battery positive electrode material was characterized by scanning electron microscopy analysis of the sodium ion battery positive electrode material prepared in Example 1. The results are as follows Figure 2 As shown, carbon is uniformly coated on the surface of the particles and presents a round block structure.
[0071] Experimental Example 3:
[0072] For the determination of discharge capacity and first coulombic efficiency, the sample and Super P conductive agent were vacuum-baked at 120 °C for 4 h. After cooling, the sample, PVDF adhesive, and Super P conductive agent were paddle-stirred into a paste at a mass ratio of 90:5:5. The paste was evenly applied on aluminum foil with a 300 μm coating and baked at 100 °C for 8 h to obtain a single-sided surface density of 50 g / m 2Electrode. The baked electrode is cut and pressed into an electrode of a certain shape, and then baked at 100 ° C in vacuum for 8 h to obtain a working electrode. Metallic sodium is cut into a sodium metal counter electrode under an argon atmosphere. The PP diaphragm is cut into a certain shape and size and then baked at 80 ° C in vacuum for 12 h to obtain the required diaphragm. The prepared working electrode and counter electrode, electrolyte and diaphragm are assembled into 5 pairs of well-sealed half-cells. The half-cell is tested on a battery program-controlled tester, and the cycle is carried out in constant current mode at a rate of 0.1C and a voltage of 2-4 V. The sample is the sodium ion battery positive electrode material obtained in Examples 1-6 and Comparative Example 1.
[0073] Table 1 Discharge capacity test results of half-cell
[0074]
[0075] Na prepared in Example 1 of the present invention 3.64 Fe 2.91 (PO4)2P2O7@C, the positive electrode material of sodium ion battery, is made into a half-cell, and its discharge capacity test results are as follows Figure 3 As shown, in Example 1, Na 3.64 Fe 2.91 (PO4)2P2O7@C can provide 118 mA h g at 0.1 C -1 The discharge capacity of the Na prepared in Example 2 of the present invention is 98.54%. 3.64 Fe 2.91 The discharge capacity provided by (PO4)2P2O7@C after being made into a half-cell is higher than that of Example 1, indicating that the use of the oleate prepared in Example 2 is better than the oleic acid used in Example 1, and further indicating that the structure of butyric acid glyceride combined with oleic acid can improve the Na 3.64 Fe 2.91 (PO4)2P2O7@C made of half-cell discharge capacity; compared with the comparative example 1, the present invention examples 2, 3, 4 show that when using oleate, the amount of oleate used will affect the Na 3.64 Fe 2.91 (PO4)2P2O7@C is used to make a half-cell with a discharge capacity of 1:1. Therefore, the oleate needs to be used in a certain amount, otherwise it cannot play a role in improving the discharge capacity of the Na 3.64 Fe 2.91 (PO4)2P2O7@C made into half-cell discharge capacity; Examples 5 and 6 of the present invention compared with Example 2 show that the use of oleate to prepare Na 3.64 Fe 2.91When (PO4)2P2O7@C is used, isooctyl palmitate can be further used. In the presence of oleic acid ester, isooctyl palmitate is further used to obtain Na 3.64 Fe 2.91 When (PO4)2P2O7@C was made into a half-cell, its discharge capacity was further improved, indicating that the addition of isooctyl palmitate can improve the 3.64 Fe 2.91 Effect of (PO4)2P2O7@C on the discharge capacity of a half-cell.
[0076] Experimental Example 4:
[0077] The capacity retention rate was measured, and the half-cells made of the sodium ion battery positive electrode materials obtained in Examples 1-6 and Comparative Example 1 were tested on a battery program-controlled tester, and the cycle was carried out in a constant current mode at a rate of 10 C and a voltage of 2-4V.
[0078] Table 2 Capacity retention test results of half-cell
[0079]
[0080] Na prepared in Example 1 of the present invention 3.64 Fe 2.91 (PO4)2P2O7@C, the positive electrode material of sodium ion battery, is made into a half-cell, and its capacity retention rate is as follows Figure 4 As shown, the Na prepared in Example 1 3.64 Fe 2.91 The half-cell made of (PO4)2P2O7@C still maintains 88.6% of its capacity after 5000 cycles at 10°C. Under the same test conditions, the capacity retention rate results of all embodiments and comparative examples are shown in Table 2. 3.64 Fe 2.91 The capacity retention rate of the half-cell made of (PO4)2P2O7@C after 5000 cycles is higher than that of Example 1, indicating that the use of the oleate prepared in Example 2 is better than the oleic acid used in Example 1, which further indicates that the structure of butyric acid glyceride combined with oleic acid can improve the capacity of Na 3.64 Fe 2.91 Capacity retention rate of half-cell made of (PO4)2P2O7@C; Compared with Comparative Example 1, Examples 2, 3, and 4 of the present invention show that when oleate is used, the amount of oleate used will affect the capacity retention rate of half-cell made of Na 3.64 Fe 2.91 (PO4)2P2O7@C has a good capacity retention rate in the half-cell, so the oleate needs to meet a certain usage amount, otherwise it cannot play a role in improving the capacity retention rate of Na 3.64 Fe2.91 (PO4)2P2O7@C made into half-cell capacity retention rate; compared with Example 2, Examples 5 and 6 of the present invention show that the use of oleate to prepare Na 3.64 Fe 2.91 When (PO4)2P2O7@C is used, isooctyl palmitate can be further used. In the presence of oleic acid ester, isooctyl palmitate is further used to obtain Na 3.64 Fe 2.91 When (PO4)2P2O7@C was made into a half-cell, its capacity retention rate was further improved, indicating that the addition of isooctyl palmitate can improve the capacity retention of Na 3.64 Fe 2.91 The effect of capacity retention of half-cell made of (PO4)2P2O7@C.
[0081] Experimental Example 5:
[0082] The capacity retention rate at 60°C was measured, and the half-cell made of the sodium ion battery positive electrode material obtained in Example 1 was tested on a battery program-controlled tester, and the cycle was carried out in constant current mode at a rate of 1 C and a voltage of 2-4 V. 3.64 Fe 2.91 (PO4)2P2O7@C, the positive electrode material of sodium ion battery, is made into a half-cell. The capacity retention rate at 60°C is as follows Figure 5 As shown, the prepared Na 3.64 Fe 2.91 The half-cell made of (PO4)2P2O7@C has a capacity retention of 100% after 200 cycles at 1 C and exhibits good thermal stability at 60 °C.
[0083] The embodiments and / or implementation methods described above are only used to illustrate the preferred embodiments and / or implementation methods for realizing the technology of the present invention, and are not intended to limit the implementation methods of the technology of the present invention in any form. Any technical personnel in this field may make slight changes or modifications to other equivalent embodiments without departing from the scope of the technical means disclosed in the content of the present invention, but they should still be regarded as technologies or embodiments that are essentially the same as the present invention.
[0084] This article uses specific examples to illustrate the principles and implementation methods of this application. The description of the above embodiments is only used to help understand the method and its core ideas of this application. The above is only the preferred implementation method of this application. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, ordinary technicians in this technical field can make several improvements, modifications or changes without departing from the principles of this application, and can also combine the above technical features in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the invention to other occasions without improvement, should be regarded as the scope of protection of this application.
Claims
1. A sodium ion battery positive electrode nanomaterial, comprising: Composite sodium iron phosphate material for the core layer and C material for the outer layer coating; The structure of the composite sodium iron phosphate material is Na x Fe y (PO4)2P2O7, wherein x is 3-3.64, and y is 1-2.91; the C material is formed by carbonization of oleic acid ester, and the oleic acid ester is made of oleic acid and butyric acid glyceride; In the preparation of oleic acid ester, oleic acid and butyric acid glyceride are mixed, and p-toluenesulfonic acid monohydrate is added as a catalyst; the mixture is stirred evenly under a nitrogen environment and reacted at 50-100° C. for 4-10 hours and then cooled to room temperature; the mass ratio of oleic acid to butyric acid glyceride is 1:1-3, and the mass ratio of p-toluenesulfonic acid monohydrate to oleic acid is 1:25-35; In the preparation of the positive electrode nanomaterial for sodium ion batteries, the composite sodium iron phosphate material and oleic acid are ball-milled and mixed under argon for 12-36 hours, dried under an inert atmosphere, and heated to 500-600°C for high-temperature carbonization for 5-15 hours; the amount of the composite sodium iron phosphate material and oleic acid ester used is a mass ratio of 1:0.5-4.
2. The sodium ion battery positive electrode nanomaterial according to claim 1, characterized in that: The x is 3.64 and the y is 2.
91.
3. A method for preparing a sodium ion battery positive electrode nanomaterial, comprising: S1: The composite sodium iron phosphate raw material is synthesized by spray drying and high temperature annealing to form the composite sodium iron phosphate material, namely Na x Fe y (PO4)2P2O7, wherein x is 3-3.64 and y is 1-2.91; S2: The composite sodium iron phosphate material and the C coating material are mixed and carbonized at high temperature to form Na x Fe y (PO4)2P2O7@C, the cathode nanomaterial for sodium-ion batteries; The C coating material includes oleate, which is made of oleic acid and butyric acid glyceride; In the preparation of oleic acid ester, oleic acid and butyric acid glyceride are mixed, and p-toluenesulfonic acid monohydrate is added as a catalyst; the mixture is stirred evenly under a nitrogen environment and reacted at 50-100° C. for 4-10 hours and then cooled to room temperature; the mass ratio of oleic acid to butyric acid glyceride is 1:1-3, and the mass ratio of p-toluenesulfonic acid monohydrate to oleic acid is 1:25-35; In the preparation of the positive electrode nanomaterial for sodium ion batteries, the composite sodium iron phosphate material and oleic acid are ball-milled and mixed under argon for 12-36 hours, dried under an inert atmosphere, and heated to 500-600 ° C for high-temperature carbonization for 5-15 hours; the amount of the composite sodium iron phosphate material and the oleic acid ester is used in a mass ratio of 1:0.5-4; The composite sodium iron phosphate raw materials include NaH2PO4·2H2O, C6H8O7·H2O, Fe(NO3)3·9H2O and water; the temperature of the spray drying method is 80-120°C; or, the high temperature annealing method is annealing at 200-400°C under argon / hydrogen flow for 2-8 hours.
4. The method for preparing a sodium ion battery positive electrode nanomaterial according to claim 3, characterized in that: The usage ratio of NaH2PO4·2H2O and water is 0.0002-0.003 mol / mL, the usage ratio of C6H8O7·H2O and water is 0.0002-0.003 mol / mL, and the usage ratio of Fe(NO3)3·9H2O and water is 0.0001-0.002 mol / mL; or, C6H8O7·H2O is citric acid monohydrate.
5. A battery comprising the sodium ion battery positive electrode nanomaterial according to any one of claims 1-2 or the sodium ion battery positive electrode nanomaterial prepared by the method according to any one of claims 3-4.
6. A vehicle comprising the battery according to claim 5.
Citation Information
Patent Citations
Carbon-nitrogen co-coated ferric phosphate sodium pyrophosphate composite material, preparation method and application
CN116364923A
Bicontinuous phase coated ferric sodium pyrophosphate positive electrode material and preparation method thereof
CN116565165A